Journal of Integrative Environmental Sciences - Journal of Integrative Environmental Sciences (Taylor & Francis, 2026)
The Journal of Integrative Environmental Sciences will be ceasing publication in December 2026. The journal is now closed to new submissions. Ongoing submissions will be processed as normal. For any questions, please contact the journal team. Journal of Integrative Environmental Sciences (JIES) publishes international research on social and natural sciences, focusing on significant environmental issues. JIES is published on behalf of the VVM, a network of environmental professionals in the Netherlands.
FI 0.43
Q3
Keywords: Biological; Earth & Environmental Food Science; Ciencia ambiental; Acuerdos transformativos; Transformative agreements; Agua; Cambio climático; Contaminación; Medio ambiente y desarrollo; Sistemas de gestión ambiental